Trichocera (Metatrichocera) gigantea Dahl 1967 - Petrašiūnas, Andrius; Podėnas, Sigitas (Zenodo, 2011)
Trichocera (Metatrichocera) gigantea (Dahl, 1967) Metatrichocera gigantea Dahl, 1967. Dahl, 1967b: 195. Trichocera ( Metatrichocera ) gigantea (Dahl, 1967). Dahl & Alexander, 1976: 14. Illustrated by Dahl, 1967b: figs. 15–19, 28–31. Material examined. MONGOLIA: 1 male, Hovsgol Aimag, Khankh Soum, Noyon river bank, N51.201528 E100.807278, altitude 1709 m, 8–15 August, 2005, Malaise trap, coll. O. Yadamsuren and S. Enkhtaivan, habitat: narrow valley with boggy forb-sedge meadow ( Carex sp., Leymus chinensis , Potentillia sp.), vegetation coverage 70 percent, malaise trap at river edge. The species was known from Sweden (Dahl, 1967), Finland (Dahl, 1968) and Arctic tundra of Russia (Lantsov & Chernov, 1987). Occurrence of species in permafrost zone of Northern Mongolia was expected, despite disjunction with the rest of the distribution area. Published as part of Petrašiūnas, Andrius & Podėnas, Sigitas, 2011, Notes on winter flies Trichoceridae (Diptera) of Mongolia with description of new species, pp. 61-68 in Zootaxa 3031 on page 62, DOI: 10.5281/zenodo.278712